Analysis of coinfections in patients with hematologic malignancies and COVID-19 by next-generation sequencing of bronchoalveolar lavage fluid - Wenxiu Shu; Qianqian Yang; Jing Le; Qianqian Cai; Hui Dai; Liufei Luo; Jiaqi Tong; Yanping Song; Bingrong Chen; Yaodong Tang; Dian Jin (European Journal of Medical Research)
Abstract Background Coinfections in patients with coronavirus disease 2019 (COVID-19) affect patient prognosis. Patients with hematologic malignancies (HMs) are usually immunosuppressed and may be at high risk of coinfection, but few related data have been reported. Here, we conducted a retrospective study to explore coinfections in patients with HMs and COVID-19 by next-generation sequencing (NGS) of bronchoalveolar lavage fluid (BALF). Methods The data of hospitalized patients with pneumonia who underwent NGS analysis of BALF were reviewed. COVID-19 patients with HMs were enrolled in the HM group, and those without HMs were enrolled in the non-HM group. The coinfections of the two groups identified by NGS were analyzed. Results Fifteen patients were enrolled in the HM group, and 14 patients were enrolled in the non-HM group. The coinfection rates in the HM group and non-HM group were 80.0% and 85.7%, respectively. The percentage of coinfected bacteria in the HM group was significantly lower than that in the non-HM group (20.0% vs 71.4%, p = 0.005). The coinfection rates of fungi and viruses were 60.0% and 35.7%, respectively, in the HM group and 35.7% and 78.6%, respectively, in the non-HM group, with no significant differences. The most common coexisting pathogen in patients with HMs was Pneumocystis jirovecii (33.3%), and the most common coexisting pathogen in patients without HMs was human gammaherpesvirus 4 (50%). Coinfection with herpesviruses occurred frequently in both groups. Conclusions Our study showed that the majority of hospitalized patients with COVID-19 are likely to be co-infected with other pathogens. Pneumocystis jiroveci and herpesvirus are commonly coinfected pathogens in patients with HMs. Bacterial coinfection is rare in patients with HMs but is more common in patients without HMs.